IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DI MAN YOGYAKARTA III - Sholihah, Hidayatus (Universitas Islam Sultan Agung, 2018)
This study is aimed at revealing the functions of human resource management in MAN Yogyakarta III (State Islamic Senior High School) that includes human resource planning, recruitment, selection and placement, training and development, performance appraisal, compensation, health program, teacher and employee relation and the effectiveness of human resource management.This study is a qualitative research. The subjects of this study are the principal, teachers, employees and students of MAN Yogyakarta III. The data were collected through participant observation, semi-structured interview and documentation. The technique employed to measure the data validity was triangulation. The research instrument was the researcher herself. The data were analyzed using interactive model consisting of three phases: data reduction, data display, and verification.The findings show that MAN Yogyakarta III (1) arranges human resource planning based on the vision, however, it is not effective because madrasah has no right to plan; (2) recruits competent teachers and employees effectively through news paper; (3) sets four types of effective selection: administration selection, academic selection, interview and micro teaching and positions the teachers and employees based on their academic qualification and competences; (4) implements effective training and development programs in accordance with the teachers` and employees` needs such as sharing ideas and knowledge, comparative study, internal presentation, evaluation and coordination; (5) appraises performance by checking the administration of teaching and supervision but the implementation of performance appraisal is not effective. (6) gives the effective compensation for the teachers and employees in accordance with their status; (7) undertakes effective health programs by creating clean and healthy school environment; (9) organizes some programs to establish effective relationship between the teachers and employees.